Effectiveness of an Instructional Design-Based Self-Management Program for Patients with Knee Osteoarthritis - Tanimura, Chika; Tokushima, Yasuko; Yoshimura, Junko; Miyoshi, Masayuki; Matsumoto, Hiromi; Morita, Tetsuji; Matsumoto, Akihiko; Ogura, Yoshifumi; Nezu, Masaru; Hagino, Hiroshi; Matsumoto, Yuka; Noma, Hisashi; et al. (Yonago acta medica, 2025)
In recent years, various psychological interventions have garnered attention as effective support methods to promote self-management and comprehensively understand those with physical and psychological problems associated with knee pain. The purpose of this study was to implement an instructional design (ID) based self-management program for outpatients diagnosed with KOA and to verify the effectiveness of the program. In this single-arm uncontrolled before‒after comparative intervention study, 41 subjects diagnosed with symptomatic knee osteoarthritis participated in an intervention program. Their pain, physical function, self-efficacy, self-care agency, and daily life difficulties were evaluated. A mixed-effects model was employed to examine the changes in each outcome from baseline to immediately before and after the intervention, and after one, three, and six months. "Pain at the beginning of walking," "pain from standing to sitting position," and "pain after long-distance walking" reduced significantly immediately after the intervention and after one month. "Pain when climbing stairs" reduced significantly immediately after the intervention and after one, three, and six months. The sit-to-stand test showed significant improvement from baseline to immediately after and one, three, and six months after the intervention. Self-care agency scores improved significantly immediately after the intervention and after one and six months. The intervention program effectively improved physical function, self-care agency, and self-efficacy, and reduced pain from one to six months. : This program could lead to an increase in the healthy life expectancy of the older adults.